2004
DOI: 10.2298/mpns0410434v
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior jaw position in persons with skeletal class I

Abstract: Differences identified in craniofacial parameters in relation to Bolton standards show that one should carefully consider the risk of altering facial esthetics of patients from Vojvodina with extraction treatment. Whenever possible, give priority to early non-extraction treatment, in order to reach the best possible end-result within the given facial type, preserving facial esthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…By examining the sagittal yaws position inpersons with skeletal class I authors found that the angle of maxillary prognathism (SNS) and angle of man-angle of mandibulary prognathism (SNB) are significantly lower than the standard values, which indicates the posterior position of yaws and retrognathic facial type [19].…”
Section: Sažetakmentioning
confidence: 99%
“…By examining the sagittal yaws position inpersons with skeletal class I authors found that the angle of maxillary prognathism (SNS) and angle of man-angle of mandibulary prognathism (SNB) are significantly lower than the standard values, which indicates the posterior position of yaws and retrognathic facial type [19].…”
Section: Sažetakmentioning
confidence: 99%